GFF Political Economy of Health System Reforms
This webinar provided the unique opportunity to hear from and exchange with Dr. Muhammad Pate, (Director of the Global Financing Facility and Global Director of the Health, Nutrition and Population Global Practice of the World Bank) on the political economy of health system reforms and, particularly, on the transformative approach of the GFF. Summary Note Video
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); development partners / parceiros de cooperação; health / saúde